2003
DOI: 10.1080/10408690390826581
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Prevention of Plant Tissue Collapse during Dehydration: A Critical Review

Abstract: The appearance and functional properties are primordial in the quality assessment of semifinished fruit and vegetable products. These properties are often associated with shrunken, shriveled, darkened materials of poor rehydration ability after been subjected to air-drying--the most used drying method in the food industry. Fruits and vegetables are cellular tissues containing gas-filled pores that tend to collapse when subjected to dehydration. Collapse is an overall term that has different meanings and scale-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 0 publications
1
62
0
4
Order By: Relevance
“…29 The details of mechanisms and prevention of plant tissue collapse during dehydration at temperatures below 50 C were covered by. 30 Three pathways of water migration were discussed: intercellular spaces, wall-to-wall, and cell-to-cell. The resistances of each pathway to transport properties were not studied; hence quantification of water diffusivity using the study is not possible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…29 The details of mechanisms and prevention of plant tissue collapse during dehydration at temperatures below 50 C were covered by. 30 Three pathways of water migration were discussed: intercellular spaces, wall-to-wall, and cell-to-cell. The resistances of each pathway to transport properties were not studied; hence quantification of water diffusivity using the study is not possible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, dried soil organic matter is more easily degraded than non-dried soil (Hayashi and Harada, 1969;Marumoto et al, 1977). Similarly, it is well known that the organic matrix of fruits and vegetables can collapse irreversibly after dehydration (Prothon et al, 2003). Here we use the drying effect on the sediment structure to investigate mechanisms of solute-solid sorption.…”
Section: Introductionmentioning
confidence: 98%
“…During the initial stage of AD, shrinkage increases rapidly; the value then slowly increases until it reaches an equilibrium point [80]. It was observed that a stronger shrinkage phenomena occurs in MW and AD dryers than in FD [77,81]. This is because the raised temperature increased the rate of cellular shrinkage following an Arrhenius-type behavior [17].…”
Section: Shrinkagementioning
confidence: 74%